Design information in managing refurbishment projects in Malaysia - Ali, Azlan-Shah (Academic Journals, 2010)
Although design cost makes up a small percent of a total project cost, the performance of refurbishment projects are normally considerably affected by design processes. The lack of information in refurbished designs becomes an obstacle for designers to complete tasks successfully during the initial stage of the design process. The objective of this study is to discuss the sources of design information in refurbishment projects. The study has also been extended to demonstrate how different sources of information can affect the performance of refurbishment design. From the results, it is concluded that a site survey was considered the most important method of obtaining design information followed by the client's brief during the design process of refurbishment projects.